PENGARUH PERMAINAN KECIL 4 2 TERHADAP KETEPATAN PASSING TIM SEPAKBOLA SD NEGERI NO.166/II TIRTA MULYA - baidi baidi (Jurnal Muara Pendidikan, 2020)
Basically, playing football requires teamwork because each team has 11 players. It is very difficult to work together if there is no team coordination training or communication between players. The author intentionally conducted this research with the aim of reducing misunderstanding between fellow 1 team players when competing and can show a beautiful game of football. This type of research is experimental research because of the pre test, treatment, and post test by looking at the independent variable and the dependent variable. The independent variable is Small Game Exercise 4 2 while the dependent variable is the Accuracy of Passing. The population in this study were all grade VI students of SD Negeri No.166 /II Tirta Mulya. The results of this study indicate that variations in passing exercises can improve passing skills supported by the results of the t-test namely tarithmetic = 5.8113> ttable = 1.725.